Nitrogen recovery from low-value biogenic feedstocks via steam gasification to methylotrophic yeast biomass - Shirvani, Roghayeh; Bartik, Alexander; Alves, Gustavo A. S.; Garcia de Otazo Hernandez, Daniel; Müller, Stefan; Föttinger, Karin; Steiger, Matthias G. (Frontiers in Bioengineering and Biotechnology, 2023)
Carbon and nitrogen are crucial elements for life and must be efficiently regenerated in a circular economy. Biomass streams at the end of their useful life, such as sewage sludge, are difficult to recycle even though they contain organic carbon and nitrogen components. Gasification is an emerging technology to utilize such challenging waste streams and produce syngas that can be further processed into e.g., Fischer-Tropsch fuels, methane, or methanol. The objective is to investigate if nitrogen can be recovered from product gas cleaning in a dual fluidized bed after gasification of softwood pellets. The methylotrophic yeast Komagataella phaffii can be used to convert this stream into yeast biomass, which provides a valuable source of protein for food and feed. It is discussed how methanol can be obtained from syngas by chemical catalysis, which is used as a carbon source for the yeast culture. Gas compositions derived from gasification of biogenic feedstocks including sewage sludge, bark, and chicken manure are evaluated for their ability to yield methanol and yeast biomass. An integrated process concept is proposed connecting gasification with methanol synthesis and bioconversion to protein-rich yeast biomass.